Analysis of Fuel Distribution at Pertashop at PT XYZ - Arifah Candra Kirana; Nurwidiana (Journal of Engineering Science and Technology Management, 2025)
PT. XYZ is a company involved in various activities related to fuel oil (BBM), such as receiving, storing, and distributing it to gasstations or Pertashop. The process of sending fuel from PT. XYZ to Pertashop is carried out using tanker trucks. One of the problemsfaced is the limited number of tanker trucks, which can cause delays in fuel delivery, so that the distribution schedule cannot be metproperly. In addition, this also reduces the time available for vehicle maintenance and increases the risk of fatigue for tanker truck drivers, which can lead to work accidents. This study aims to find an effective fuel delivery route so that travel time is shorter, so that fuel delivery to various locations can run well and on time. Using the Nearest Neighbor Method, this study can produce a more efficient solution in terms of saving distance when compared to the route currently used by the company. The proposed route with the Nearest Neighbor method has a total distance of 5268.3 km, which is a decrease of 14.49% from the current total distance. The Nearest Neighbor method can also result in savings in the number of tanker trucks, which initially used 119 trucks for 14 days, consisting of 88 tanker trucks with a capacity of 8,000 L and 31 tanker trucks with a capacity of 16,000 L. 41 tanker trucks with a capacity of 16,000 L, which has a savings in the number of tankers of 13.44%